The Hersfeldensis and Fuldensis of Ammianus Marcellinus: a reconsideration - Stover, J; Kelly, G (Cambridge University Press, 2016)
The only two authoritative manuscripts of Ammianus Marcellinus to survive to the present day were produced in Germany in the first half of the ninth century: Vaticanus Latinus 1873 from Fulda (V), and a fragmentary manuscript from Hersfeld now preserved in Kassel (M). This article challenges the consensus that V is a copy of M; taking into account recently uncovered fragments of M (new transcriptions of which are offered in the appendix), we argue that both are copies of the same damaged original, and discuss the implications for the editing of Ammianus and for our understanding of Carolingian scholarship.